Policy of Sultan of Langkat in Managing and Keeping the Environment of Langkat Area - Ratna Ratna; Suprayitno Suprayitno; Farida Hanum Ritonga; Handoko Handoko (Budapest International Research and Critics University, 2019)
Long before modern regulations on the environment were implemented, Malay sultanates on the East Coast of Sumatra had made regulations that protect, manage and preserve the environment within their territories. One of the sultanates that has these regulations is the Langkat Sultanate. Environmental management in the Langkat Sultanate includes protection and management of forests, river protection, and prohibition of logging certain types of trees and protecting animals. How does the Sultan of Langkat protect and manage the environment? What kind of environment is protected and managed by the Sultan of Langkat? These questions will be discussed in writing. This paper uses archival sources and publications during the colonial government in the Netherlands in Langkat and the rules of the Sultan of Langkat itself about environmental management and protection. This paper aims to describe how traditional governance including the Langkat Sultanate has managed and maintained the environment well.